PENGARUH KAMPANYE HITAM MELALUI MEDIA SOSIAL YOUTUBE NET.NEWSROOM TERHADAP PERILAKU PEMILIH MASYARAKAT PEMILIH JOKOWI DI KELURAHAN KAYU PUTIH PULOGADUNG JAKARTA TIMUR PADA PILPRES 2019 - Raihan Tristan Saputra (2024)
This research aims to discuss the influence of the black campaign via YouTube on the voter's behavior of Jokowi's voters in Kayu Putih, Pulogadung, East Jakarta in the 2019 presidential election. By using the black campaign theory put forward by Thomas Jay C and Michel Hersen and the concept of voter behavior according to Kristiadi. This research uses a quantitative approach and uses simple linear regression analysis to test the research hypothesis. The sampling technique in this research uses a non-probability quota sampling technique by first classifying potential respondents before filling in the research questionnaire data. The data collection method used was a survey by sending an online questionnaire in the form of a Google form to samples residing at TPS 064 Kayu Putih. The results and conclusions of this research are that there is a weak influence between black campaigning via YouTube on voter behavior at TPS 064 Kayu Putih, Pulogadung, East Jakarta, which is mostly based on a rational approach.